RISK-MANAGEMENT IN THE ANTI-CRISIS REGULATION OF INSURANCE INDUSTRY - G. A. Nasyrova (Real Economics Publishing House, 2014)
It is considered risk-management of the insurance company as the element of anti-crisis regulation at the microlevel, realized in anti-crisis management. The program of technical risk management is made with a glance a life-cycle of the insurance company. The presented approach assumes inclusion in the management program of investment, currency, social and other risks of the insurance activity.